2018
DOI: 10.1139/cjas-2017-0126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a blend of organic acids and medium-chain fatty acids with and without Enterococcus faecium on growth performance, nutrient digestibility, blood parameters, and meat quality in finishing pigs

Abstract: An experiment was conducted to assess effects of Enterococcus faecium and a blend of organic acids (OAs) and medium-chain fatty acids (MCFAs) in finishing pigs. A total of 120 pigs [Duroc × (Yorkshire × Landrace); 51.04 ± 1.82 kg] were randomly assigned to five dietary treatments: CON, basal diet; BOM1, CON + 500 mg kg−1 blend of OAs and MCFAs; BOM2, CON + 1000 mg kg−1 blend of OAs and MCFAs; EBOM1, BOM1 + 20 mg kg−1 E. faecium; EBOM2, BOM2 + 20 mg kg−1 E. faecium. Pigs fed EBOM1 and EBOM2 diets had higher ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…This reason could be explained for the current Advances in Animal and Veterinary Sciences study, which indicates that the dietary supplementation with a combination of PROB and ORAC had positive synergism effects on growth performance and FCR than the supplementation with PROB or ORAC alone. These results were confirmed by (Lei et al, 2018).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 69%
See 1 more Smart Citation
“…This reason could be explained for the current Advances in Animal and Veterinary Sciences study, which indicates that the dietary supplementation with a combination of PROB and ORAC had positive synergism effects on growth performance and FCR than the supplementation with PROB or ORAC alone. These results were confirmed by (Lei et al, 2018).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 69%
“…Eubiotics are referred as a healthy balance of microflora in the gastrointestinal tract (Nowak et al, 2017). Several types of eubiotics, such as organic acids, essential oil compounds, and probiotics, have been shown to have a positive effect on gut health and overall animal performance (Agboola et al, 2015;Zhang et al, 2016;Lei et al, 2018). However, the extent of the positive effects is variable depending on the products used.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al also investigated how a blend of matrixcoated organic acids and MCFAs, without or with a probiotic (Enterococcus faecium), affected the growth performance of finishing pigs [83]. The feed supplement mixture contained 17% fumaric acid, 13% citric acid, 10% malic acid, 0.6% capric acid, and 0.6% caprylic acid, and the mixture was incorporated at 0.05% or 0.1% of the diet (equivalent to~0.005-0.01% total MCFAs), without or with 0.002% probiotic.…”
Section: Mcfa and Probiotic Mixturesmentioning
confidence: 99%
“…The diarrhea incidence in weanling pigs challenged with E. coli was reduced by supplementation with an OA-MCFA (C8:0, C10:0) blend [ 90 ]. When the OA-MCFA blend is added with Enterococcus, dry matter improvement had been found in finishing pigs [ 91 ]. Casellas et al instead found that minimal supplementation of MCT long chain triglyceride (LCT) could improve the survival of the smallest piglets [ 92 ].…”
Section: Fatty Acidsmentioning
confidence: 99%